(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2019)
The article focuses on the structure, content, peculiarities of constructing the dictionary of Ukrainian phraseologisms, which represent the non-verbal communication of speakers. It also outlines the basic principles and fundamentals of making lexicographic works. In particular, this paper represents the dictionary specifics in terms of the type and purpose, the way of the language unit representation, the approximate list of the fixed phraseological units, the general concept of the presenting the material in the dictionary article. A dictionary project transfers the mental and ethnic identity of Ukrainians through the prism of non-verbal communication. This is the first attempt to register the phraseological units identifying gestures, facial expressions, poses, moves, communicatively meaningful movements, etc. The paper gives reviews of the basic principles of national and foreign dictionary writing, the principles of lexicography, which include the continuity of lexicographic works, the role of the subjective factor in the process of creating a dictionary, the selection of language units, and the pragmatism of similar research works. Particular attention is paid to the principle of anthropocentrism, which is implemented in the way of multiple registering the material, taking into account the information of different branches of science (linguistics, psychology, cultural studies, ethics, non-verbal semiotics, etc.). According to the principles of dictionary creating, its main tasks, the purposes of creation, lexicographic functions are identified. Moreover the paper determines the addressee of the phraseological work, who can use the information contained therein, according to the research needs nvestigating the Ukrainian communicative space, culture, traditions, national character and world outlook, etc. The methodological fundamentals of the dictionary comprise the connection of modern phraseological studies with lexicographic traditions. As a result the reasons for listing the language units into the dictionary article are implemented due to the interpretation of the “phraseologism” term, represented in Ukrainian academic works studying phraseology problems. The analysis of researching papers allows enumerating the advantages of this dictionary type, which include actual information from other Eastern Slavic languages, encyclopaedic information, illustrations that enable the future reader to find out the cultural, linguistic and ethnographic aspects of Ukrainian phraseology.